The neuroregenerative effects of topical decorin on the injured mouse cornea - Mengliang Wu; Laura E. Downie; Liam M. Grover; Richard J. A. Moakes; Saaeha Rauz; Ann Logan; Haihan Jiao; Lisa J. Hill; Holly R. Chinnery (Journal of Neuroinflammation, 2020)
Abstract Background The cornea is innervated with a rich supply of sensory nerves that play important roles in ocular surface health. Any injury or pathology of the corneal nerves increases the risk of dry eye disease and infection. This study aims to evaluate the therapeutic potential of topical decorin to improve corneal nerve regeneration in a mouse model of sterile epithelial abrasion injury. Methods Bilateral central corneal epithelial abrasions (2-mm, Alger Brush) were performed on young C57BL/6 J mice to remove the corneal sensory nerves. Decorin, or vehicle, was applied topically, three times per day for 1 week or every 2 h for 6 h. Spectral-domain optical coherence tomography was performed to measure the abrasion area and corneal thickness. Wholemount immunofluorescence staining was used to assess sensory nerve regeneration (β-tubulin III) and immune cell density (CD45, Iba1, CD11c). To investigate the specific role of dendritic cells (DCs), Cx3cr1gfp/gfp mice, which spontaneously lack resident corneal epithelial DCs, were also investigated. The effect of prophylactic topical administration of recombinant human decorin (applied prior to the abrasion) was also investigated. Nerve tracing (NeuronJ software) was performed to compare recovery of basal nerve axons and superficial nerve terminals in the central and peripheral cornea. Results At 6 h after injury, topical decorin application was associated with greater intraepithelial DC recruitment but no change in re-epithelialisation or corneal thickness, compared to the vehicle control. One week after injury, sub-basal nerve plexus and superficial nerve terminal density were significantly higher in the central cornea in the decorin-treated eyes. The density of corneal stromal macrophages in the decorin-treated eyes and their contralateral eyes was significantly lower compared to saline-treated corneas. No significant improvement in corneal nerve regeneration was observed in Cx3cr1gfp/gfp mice treated with decorin. Conclusions Decorin promotes corneal epithelial nerve regeneration after injury. The neuroregenerative effect of topical decorin was associated with a higher corneal DC density during the acute phase, and fewer macrophages at the study endpoint. The corneal neuroregenerative effects of decorin were absent in mice lacking intraepithelial DCs. Together, these findings support a role for decorin in DC-mediated neuroregeneration following corneal abrasion injury.